Newspaper coverage of South African tobacco issues, 1997-2001 - Gladys Phaswana; Karl Peltzer (Acta Academica, 2003)
The purpose of this study was to investigate the way in which the tobacco issue has been framed in the mass media in South Africa. 363 South African newspaper articles published from January 1997 to December 2001 were analysed. Of the 224 articles finally selected for analysis, 100 were in line with the tobacco interest group and 124 supported the tobacco control group. The dominant frames used by the tobacco industry included “good product for the economy”, “concern about teenagers and youth”, “government’s role in reducing marketing visibility and destruction of jobs” and “discrimination and segregation”. The dominant frames used by the tobacco control advocates included “death/diseases”, “innocent children”, “smokers in great danger”, “glamourisation of smoking; intentional lie”, “passive smokers’ rights” and “smoking areas”. A major finding is that the frames used by both the tobacco control movement and the tobacco industry have changed over time. The tobacco industry has been steadfast in consistently targeting core human values as its dominant framing tactic. The finding may have implications for developing more effective arguments for tobacco policies.